Aplikasi Penginputan Data dan Nilai Siswa Pada SDS Nurul Huda Menggunakan Kodular dan Airtable - Alda, Muhamad; Tanjung, Sunilfa Maharani; Abdillah, Muhammad Oemar; Melsya, Laura (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
SDS Nurul Huda is a private elementary school located at Jl. Sei Serayu No 38, Babura, District of Medan Sunggal, City of Medan, North Sumatra Province. This school has been operating since 1978. Currently, student data entry and grading at SDS Nurul Huda are still done manually. Some teachers face difficulties in inputting data and grading due to it being time-consuming, especially for older teachers who struggle with reading numbers. Errors in writing student data and grades also frequently occur. This research aims to develop a data entry and grading application for students as a solution to enhance efficiency in school administration processes and replace the manual system, which is often prone to errors and time-consuming in data entry and grading. The outcome of this research is an Application for Data Entry and Grading for SDS Nurul Huda to facilitate teachers in swiftly and easily inputting student data and grades.